2022
DOI: 10.1016/j.cmi.2021.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Real-world safety data for the Pfizer BNT162b2 SARS-CoV-2 vaccine: historical cohort study

Abstract: Objective The Pfizer BNT162b2 vaccine showed a reassuring safety profile in clinical trials, but real-world data are scarce. Bell’s palsy, herpes-zoster, Guillain-Barré syndrome (GBS) and other neurological complaints in proximity to vaccination have received special public attention. We compared their rates among vaccinated and unvaccinated individuals. Methods Individuals ≥16 years vaccinated with at least one dose of BNT162b2 were eligible for this historical-cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
55
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 17 publications
2
55
1
Order By: Relevance
“…A recent Image 2 Sagittal T2 of cervical (a), thoracic (b), and lumbar (c) spines showing normal appearance of spinal cord, conus medullaris, and cauda equina large population-level study assessing the safety of BNT162b2 (another mRNA vaccine) found no association with Bell's palsy, herpes zoster, or GBS. [13] Furthermore, it is important to realize there are several reported cases of neurological complications such as transverse myelitis and GBS after COVID-19 infection. [14][15][16] After reviewing the occurrences of GBS, the Advisory Committee on Immunization Practices of the United States in July 2021 determined that the benefits of COVID-19 vaccination in preventing COVID-19 morbidity and mortality outweigh the risks for these rare serious adverse events [https:// www.…”
Section: Discussionmentioning
confidence: 99%
“…A recent Image 2 Sagittal T2 of cervical (a), thoracic (b), and lumbar (c) spines showing normal appearance of spinal cord, conus medullaris, and cauda equina large population-level study assessing the safety of BNT162b2 (another mRNA vaccine) found no association with Bell's palsy, herpes zoster, or GBS. [13] Furthermore, it is important to realize there are several reported cases of neurological complications such as transverse myelitis and GBS after COVID-19 infection. [14][15][16] After reviewing the occurrences of GBS, the Advisory Committee on Immunization Practices of the United States in July 2021 determined that the benefits of COVID-19 vaccination in preventing COVID-19 morbidity and mortality outweigh the risks for these rare serious adverse events [https:// www.…”
Section: Discussionmentioning
confidence: 99%
“…The only outcome showing an association with vaccination in the study by Shasha et al ( 1 ) was an excess of reports of numbness and tingling in BNT162b2 vaccinees mainly involving the face. This finding is difficult to interpret and warrants further investigation.…”
mentioning
confidence: 87%
“…Safety signals can be generated from pre-licensure trials or during vaccine implementation from reports of unexpected or rare clinical events that occur in temporal association with vaccination. The accompanying paper in this edition by Shasha et al ( 1 ) provides a nice “real-world” example of this process. The authors used electronic records from the Meuhedet Health Maintenance Organisation (HMO) in Israel to investigate various safety signals raised for the BNT162b2 mRNA vaccine from pre-licensure trials and post-marketing case reports.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A number of papers have examined the onset of adverse events, such as those described above, after COVID-19 vaccination. However, these recent studies have either (i) been limited to the reporting of incidence rates and otherwise lacking statistical analyses [ 18 , 19 ], (ii) unable to reach strong conclusions because of sparse data [ 20 , 21 ], or (iii) been unable to find statistically significant deviations in the occurrences of the adverse conditions described above [ 22 , 23 ]. To address these limitations, we have examined the number of cases of CVST, GBS, myocarditis or pericarditis after vaccination with either the Pfizer/BioNTech, Moderna, or J&J vaccines; in particular, we used the Vaccine Adverse Event Reporting System (VAERS), and the statistical properties of the occurrences of these post-vaccination side effects were quantified using odds ratios (ORs).…”
Section: Introductionmentioning
confidence: 99%